2012
DOI: 10.1523/jneurosci.1816-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Light-Mediated Control of Rhodopsin Movement in Mosquito Photoreceptors

Abstract: Multiple mechanisms contribute to a photoreceptor's ability to adapt to ambient light conditions. The mosquito Aedes aegypti expresses the long wavelength rhodopsin Aaop1 in all R1–6 photoreceptors and most R8 photoreceptors. These photoreceptors alter the cellular location of Aaop1 and reorganize their photosensitive rhabdomeric membranes on a daily basis. During daylight periods, Aaop1 is excluded from the light sensitive rhabdomeres and localized to multi-vesicular bodies (MVBs) within the photoreceptor cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 23 publications
2
36
0
Order By: Relevance
“…An even more dramatic light-dependent downregulation of rhabdomeral opsin levels than reported here has been described in white-eyed mutants of the mosquito Aedes aegypti (AeOps1) (Hu et al, 2012). In the mosquito, opsin removal is probably similar to LDS described here; however, unlike in Limulus, rhabdomeral opsin levels in the mosquito appear to be regulated entirely by light and dark.…”
Section: Rhops1-2 Levels Are Regulated By Complex Interactions Betweesupporting
confidence: 71%
“…An even more dramatic light-dependent downregulation of rhabdomeral opsin levels than reported here has been described in white-eyed mutants of the mosquito Aedes aegypti (AeOps1) (Hu et al, 2012). In the mosquito, opsin removal is probably similar to LDS described here; however, unlike in Limulus, rhabdomeral opsin levels in the mosquito appear to be regulated entirely by light and dark.…”
Section: Rhops1-2 Levels Are Regulated By Complex Interactions Betweesupporting
confidence: 71%
“…Horridge et al, 1981;Fleissner, 1982). Lightinduced movement of visual pigment and circadian changes in visual pigment levels have been demonstrated in mosquito photoreceptors (Hu et al, 2012). Differing secondary green sensitivity in the locust might, therefore, not be phase dependent, but daytime dependent.…”
Section: Phase-dependent Differences In Spectral Sensitivitymentioning
confidence: 99%
“…Aaop1 is the major rhodopsin of the adult compound eye because it is expressed in all R1-R6 photoreceptors and most R8 photoreceptors (Hu et al, 2012). We made use of a larval whole-mount preparation to determine the onset of Aaop1 rhodopsin expression in the developing compound eye.…”
Section: Rhodopsin Expression In the Developing Adult Eyementioning
confidence: 99%
“…Three of these groups are labeled as long-wavelength (>500 nm), short-wavelength (400-500 nm), and UV-sensitive rhodopsin (<400 nm), and two of these groups contain uncharacterized family members. We previously characterized the patterns of rhodopsin expression in the adult Aedes compound eye (Hu et al, 2009(Hu et al, , 2011(Hu et al, , 2012(Hu et al, , 2014. These studies revealed features of the visual system in Aedes that were not predicted from study of other invertebrate models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation